A conceptual article on digital technology in broadcasting / Fakrulnizam Jafri ... [et al.] - Jafri, Fakrulnizam; Abd Rahman, Nur Izzati Iwani; Kamaruzaman, Muhammad Khairil Khusyairi; Che Ismail, Nurmaheran (Faculty of Communication & Media Studies, 2022)
The conceptual article discusses digital technology in the field of the broadcasting industry. Rice (2003) stated that the term digital technologies refers to a wide variety of technologies, tools, services, and applications that make use of different kinds of computer hardware and computer software. The digitalization of the broadcasting system comprises three types of vibrant elements in production equipment, transmission equipment, and reception equipment. The broadcasting chain consists of a set of television and radio stations to transmit the same program at the same time to a huge geographical area in a way that anyone can receive via audio-video material. It is of the greatest importance to prevent troublesome issues from occurring inside the broadcasting series. In a radio broadcast, Tan et al. (2019) explained that there is a distinction between the traditional radio and the digital connections, stating that the traditional radio is over the air and is not dependent on the digital connections and that it is able to be received during power outages without a bandwidth limit. In the digital age, countries with inadequate internet access have a comparatively low penetration level due to the limited availability of the internet.